2013
DOI: 10.1002/2013jd019886
|View full text |Cite
|
Sign up to set email alerts
|

Elemental carbon measurements in European Arctic snow packs

Abstract: [1] Black carbon (BC) and other light-absorbing particles deposited on snow and ice are known to perturb the surface radiative balance. There are few published observations of the concentration of these particles in the snow in Scandinavia and the European Arctic. We measured BC concentrations in snow samples collected in this region from 2007 to 2009, and we present the results here. The data set includes 484 surface samples and 24 column samples (covering the accumulation season) from snow on land, glaciers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 82 publications
9
96
0
Order By: Relevance
“…1) on Holtedahlfonna. Forsström et al, 2013;Delaney et al, 2015). Consequently, the similarity in EC concentrations measured at stake 10 (2015 coring site) from the surface snow, snow pack and firn core samples gives confidence on the reproducibility of the used EC analysis method.…”
Section: Post-depositional Processes Affecting Ec Deposition At the Tmentioning
confidence: 86%
“…1) on Holtedahlfonna. Forsström et al, 2013;Delaney et al, 2015). Consequently, the similarity in EC concentrations measured at stake 10 (2015 coring site) from the surface snow, snow pack and firn core samples gives confidence on the reproducibility of the used EC analysis method.…”
Section: Post-depositional Processes Affecting Ec Deposition At the Tmentioning
confidence: 86%
“…As black carbon (BC) effectively absorbs visible radiation, it causes acceleration in the growth of snow grains, and therefore an overall decrease in albedo. In particular, Hansen et al (2005) suggested that the effect of BC on snow albedo contributes substantially to rapid warming and sea ice loss in the Arctic, although recent measurements (Forsström et al, 2009(Forsström et al, , 2013Doherty et al, 2010) have shown substantially lower levels of BC than was observed in the 1980s (Clarke and Noon, 1985). In view of these findings, parameterizations of BC and soot concentration in snow have been recently developed (Flanner and Zender, 2006;Yasunari et al, 2011;Aoki et al, 2011).…”
Section: Aerosol Deposition On Snow and Icementioning
confidence: 99%
“…Huang et al (2011) showed BC-in-snow concentrations decrease rapidly towards the northeast and away from major industrial regions. In the Arctic, Doherty et al (2010) and Forsstrom et al (2013) showed that the spatial differences in BC depended on the emission source intensity, the distance from the source to the deposition region, and the prevailing wind direction. In the eastern Sierra Nevada, Sterle et al (2013) noted that BC concentrations in aged snow were enhanced seven-fold relative to those in fresh snow.…”
Section: Introductionmentioning
confidence: 99%